Fluid-to-Solid Transition of Hard Regular Polygons - Anderson, Joshua A.; Antonaglia, James; Millan, Jaime A.; Engel, Michael; Glotzer, Sharon C. (ISRN Condensed Matter Physics, 2016)
Characterizing the fluid-to-solid transition (conversely the melting transition) of two-dimensional systems is a fundamental problem in condensed matter physics that has advanced significantly through the application of computational resources and algorithms. Here we report a comprehensive simulation study of the phase behavior near the melting transition of all hard regular polygons with 3≤n≤14 vertices using massively parallel Monte Carlo simulations of up to one million particles. We find that regular polygons with seven or more edges behave like hard disks and melt continuously from a solid to a hexatic fluid and then undergo a first-order transition from the hexatic phase to the fluid phase. Strong directional entropic forces align polygons with fewer than seven edges and improve local ordering in the fluid. These forces can enhance or suppress the discontinuous character of the transition depending on whether the local order in the fluid is compatible with the local order in the solid. Triangles, squares, and hexagons exhibit a KTHNY-type continuous transition between fluid and hexatic, tetratic, and hexatic phases, respectively, and a continuous transition from the appropriate x-atic to the solid. In contrast, pentagons and plane-filling 4-fold pentilles display a one-step first-order melting of the solid to the fluid with no intermediate phase. The thirteen studied systems thus comprise examples of three distinct two-dimensional melting scenario